Experimental Investigation and Control of a Hybrid (PV-Wind) Energy Power System - Mustafa, G.; Baloch, M. H.; Qazi, S. H.; Tahir, S.; Khan, N.; Mirjat, B. A. (Engineering, Technology & Applied Science Research, 2021)
The most essential infrastructure of today’s modern civilization is the energy system. A new energy revolution is ongoing worldwide in understanding the affordability, reliability, and sustainability of energy supply. One of the major challenges and opportunities considered in this energy revolution is the integration of the energy system. The varying dynamics of renewable energy production and the environmental conditions between the different energy sources are the major reasons for this challenge. Wind and solar energies are considered the best renewable sources and the foremost substitute sources for power generation. These energies are playing a vital role as alternates of nuclear energy and fossil fuels. Electricity is generated through wind energy conversion systems and photovoltaic (PV) cells. These technologies are clean and environmentally friendlier than non-renewable energies. A hybrid PV-wind generation system is more effective and consistent than a single-source system because the solar system cannot work at night or in cloudy weather while the wind speed is variable. The current study proposes an experimental-based analysis. The hardware used is the Squirrel Cage Induction Generator (SCIG) and solar panels. A boost converter is added for Maximum Power Point Tracking (MPPT) at variable wind speed and available sunlight.